MANAJEMEN STRATEGI PEMASARAN DIGITAL MELALUI MEDIA SOSIAL DALAM MENINGKATKAN VISIBILITAS DAN DAYA TARIK PESANTREN - Alfina Lutfiatun; M. Nur Fauzi (Benchmarking: Jurnal Manajemen Pendidikan Islam, 2024)
This research aims to analyze digital marketing strategy management through social media in increasing the visibility and attractiveness of Islamic boarding schools. The focus of this research is to explore how Islamic boarding schools can utilize social media, such as Instagram, Facebook, and YouTube, to introduce themselves and attract the attention of prospective students. The method used is a descriptive qualitative approach with in-depth interviews with Islamic boarding school managers, students, and students' parents, as well as observations of social media content published by Islamic boarding schools. Data collection techniques were carried out through interviews and direct observation of Islamic boarding school social media accounts. The collected data was then analyzed using thematic analysis and content analysis techniques to identify the main themes and patterns in the use of social media. The research results show that the use of attractive visual and video content, together with testimonials and reviews from alumni and parents of students, plays a significant role in increasing the visibility of Islamic boarding schools and building a positive image in the eyes of the audience. In addition, an integrated digital marketing strategy via social media has proven effective in increasing the attractiveness of Islamic boarding schools, building trust, and expanding the reach of the Islamic boarding school education market. This research suggests that Islamic boarding schools need to optimize the use of social media as a strategic and adaptive marketing tool for technological developments.